2020
DOI: 10.1111/1756-185x.13880
|View full text |Cite
|
Sign up to set email alerts
|

Common variants in IL17F gene contributed to the risk of hip osteoarthritis susceptibility in Han Chinese population

Abstract: Osteoarthritis (OA) is a chronic degenerative joint disease that is characterized by articular cartilage loss, synovial inflammation and structural changes in the subchondral bone. 1 This type of derangement and destruction of joint integrity in OA occurs in the knee and hip in humans and shows clinical symptoms, such as joint pain, dysfunction, stiffness, activity limitations and physical disability. 2 Primary hip osteoarthritis (HOA) is defined as degeneration of the tissues of the hip joint, including hyali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…To resolve this Lee and Song conducted a meta-analysis of eight studies and concluded that rs2275913 in IL17A and rs763780 in IL17F are associated with general OA, but the latter not with hip OA (HOA) 13 . However in a more recent study, rs763780 was associated with HOA in a Han Chinese population 14 , indicating that perhaps ethnicity is partially responsible for the contradictory associations of IL17 genes with OA.…”
Section: Geneticsmentioning
confidence: 88%
“…To resolve this Lee and Song conducted a meta-analysis of eight studies and concluded that rs2275913 in IL17A and rs763780 in IL17F are associated with general OA, but the latter not with hip OA (HOA) 13 . However in a more recent study, rs763780 was associated with HOA in a Han Chinese population 14 , indicating that perhaps ethnicity is partially responsible for the contradictory associations of IL17 genes with OA.…”
Section: Geneticsmentioning
confidence: 88%
“…The IL17F rs763780 C allele has been associated to an increased risk of autoimmune and inflammatory diseases such as rheumatoid arthritis in Tunisian population [32], inflammatory arthritis in a meta-analysis conducted in Caucasians [33], hip osteoarthritis in Han Chinese [34], knee osteoarthritis in Iranians [35], and psoriasis an Asians [36]. Regarding SpA, the IL17F polymorphism was associated with susceptibility to AS, disease activity and functional status in Turk patients [37], and a risk factor for SpA, AS and PsA in Brazilians [13].…”
Section: Discussionmentioning
confidence: 99%